Improving lecturers’ competence in preparing lesson plans of soil test laboratory and building information management - Rahmadona, Efrilia; Putra, M. Sang Gumilar Panca; Praditya , M. Norca; Marpen, Rio; Amalia, Kiki Rizky; Uwais, M. Abdullah (Journal of Community Service and Empowerment, 2022)
The insufficient number of lecturers and laboratory assistants has become one of the obstacles faced by STT Pagaralam. In addition, the limited ability of lecturers in mastering Soil Mechanics laboratory equipment and the absence of Semester Learning Plans (RPS) that follow the learning format are still obstacles. The purpose of this community service is to improve the competence of lecturers in preparing the RPS for the soil test laboratory and building Information management. The method used to carry out this community service were workshops and seminars. It was initiated by giving a seminar on the introduction of building information management application followed by 20 students and continued by providing training on the use of tools for five laboratory assistants and the preparation of Semester Learning Plans for five lecturers. The results of the service implementation based on the participant satisfaction questionnaire shows an increase in knowledge on the application of building information management and an increase in competence using laboratory equipment. In addition, the training participants were also provided with modules.